Predicting the Effects of Waning Vaccine Immunity Against COVID‐19 through High‐Resolution Agent‐Based Modeling (Adv. Theory Simul. 6/2022). Issue 6 (10th June 2022) - Truszkowska, Agnieszka; Zino, Lorenzo; Butail, Sachit; Caroppo, Emanuele; Jiang, Zhong‐Ping; Rizzo, Alessandro; Porfiri, Maurizio
Abstract : Predicting the Effects of Waning Vaccine Immunity Against COVID‐19 through High‐Resolution Agent‐Based Modeling Mathematical models have proven to be indispensable in our fight against COVID‐19. In article 2100521, Agnieszka Truszkowska, Maurizio Porfiri, and co‐workers expand on a high‐resolution agent‐based model published previously in this journal to study the effectiveness of the booster shot campaign in preventing new COVID‐19 waves in the town of New Rochelle, NY. Image by Anna Sawulska and Maurizio Porfiri.